Non-Enzymatic Co3O4 Nanostructure-Based Electrochemical Sensor for H2O2 Detection - Mizers, V.; Gerbreders, V.; Krasovska, M.; Sledevskis, E.; Mihailova, I.; Ogurcovs, Andrejs; Bulanovs, A.; Gerbreders, Andrejs (Sciendo, 2023)
This article describes the synthesis of nanostructured cobalt oxide on iron wires and its application for the detection of hydrogen peroxide as working electrode for non-enzymatic electrochemical sensor. Cobalt oxide was obtained by the hydrothermal synthesis method using chloride and acetate anions. The resulting nanostructured coating obtained from the chloride precursor is a uniform homogeneous porous network of long nanofibers assembled into regular honeyсomb-like formations. In the case of an acetate precursor, instead of nanofibers, petal-like nanostructures assembled into honeycomb agglomerates are observed. The structure, surface, and composition of the obtained samples were studied using field-emission scanning electron microscopy along with energy-dispersive spectroscopy and X-ray diffractometry. The resultant nanostructured specimens were utilized to detect H2O2 electrochemically through cyclic voltammetry, differential pulse voltammetry, and i-t measurements. A comparative research has demonstrated that the nanostructures produced from the chloride precursor exhibit greater sensitivity to H2O2 and have a more appropriate morphology for designing a nanostructured sensor. A substantial linear correlation between the peak current and H2O2 concentration within the 20 to 1300 μM range was established. The Co3O4 electrode obtained exhibits a sensitivity of 505.11 μA·mM−1, and the electroactive surface area is calculated to be 4.684 cm2. Assuming a signal-to-noise ratio of 3, the calculated limit of detection is 1.05 μM. According to the interference study, the prevalent interfering agents, such as ascorbic acid, uric acid, NaCl, and glucose, do not influence the electrochemical reaction. The obtained results confirm that this sensor is suitable for working with complex analytes.The actual sample assessment demonstrated a recovery rate exceeding 95 %. --//-- This is an open access article Mizers, V., Gerbreders, V., Krasovska, M., Sledevskis, E., Mihailova, I., Ogurcovs, A., Bulanovs, A. and Gerbreders, A.. "Non-Enzymatic Co3O4 Nanostructure-Based Electrochemical Sensor for H2O2 Detection" Latvian Journal of Physics and Technical Sciences, vol.60, no.6, 2023, pp.63-84. https://doi.org/10.2478/lpts-2023-0037 published under the CC BY-NC-ND 4.0 licence.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Electrochemical sensor; cobalt oxide; cyclic voltammetry; hydrogen peroxide; nanostructures